Republic of Azerbaijan : Fifth Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the Fifth Review Under the Poverty Reduction and Growth Facility for the Republic of Azerbaijan focuses on the short-term macroeconomic outlook and monetary and exchange rate policies. Domestic demand has been increasing much faster than GDP partly on account of large oil sector-related and other investments. There was broad agreement that greater exchange rate flexibility is essential for reducing inflation pressures. Azerbaijan has had an excellent track record in servicing its external debt.